KIERKEGAARD AND EVANS ON THE PROBLEM OF ABRAHAM - Manis, R. Zachary (Journal of religious ethics, 2011)
A significant challenge faces any ethic that endorses the view that divine commands are sufficient to impose moral obligations; in this paper, I focus on Kierkegaard's ethic, in particular. The challenge to be addressed is the “modernized” problem of Abraham, popularized especially by Fear and Trembling: the dilemma that an agent faces when a being claiming to be God issues a command to the agent that, by the agent's own lights, seems not to be the kind of command that a loving God would issue. Against a solution to this problem proposed by C. Stephen Evans in Kierkegaard's Ethic of Love, I argue that Kierkegaard regards this scenario as never actually resulting in a fully responsible agent's performance of some horrendous action on account of her non-culpable misinterpretation of God's will and/or failure to discern correctly whether a perceived moral imperative truly is divine in origin.